SOSIALISASI KONSTRUKSI SOSIAL SEKOLAH KEARAH INKLUSIF PADA KEPALA SEKOLAH SD SE KECAMATAN BANTAENG - Awayundu; Mustafa Mustafa; Faizal Faizal; Nurazizah Rahmi (PT Ininnawa Paramacitra Edu, 2026)
The Social Construction Socialization Towards Inclusion conducted in Bantaeng District was presented as an effort to transform the paradigm of Elementary School Principals from the Medical Model of Disability to the Social Model of Disability. The main problem was the gap between policy and practice, marked by low managerial understanding and a school culture that was not yet inclusive. This activity aimed to improve understanding of practical competencies. The implementation method was packaged in the form of workshops and mentoring. The results of this activity showed a significant increase from the category of 'Poor' to 'Good' and managerial competency from Sufficient to Very Good, proving the success of shifting social construction towards inclusive practices.